The peak-shift method for the description of structural relaxation in glassy materials: a critical review - Svoboda, Roman (Wiley-Blackwell, 2023)
Nowadays, the glass transition kinetics is most commonly described in terms of the Tool-Narayanaswamy-Moynihan (TNM) model. Evaluation of one of the most prominent features of the structural relaxation motions-the relaxation nonlinearity-was traditionally done using the peak-shift (PS) method. This paper introduces, for the first time, extensive testing of the PS method by means of theoretical simulations for all practically observable types of structural relaxation behavior and all types of glassy/amorphous materials (tested range of the glass transition temperatures: -55 to 1000 degrees C; tested range of the relaxation activation energies: 300-1300 kJ.mol(-1)). For the majority of types of structural relaxation behavior, the PS method tends to slightly overestimate the value of the TNM nonlinearity parameter chi(by similar to 0.05-0.10). In the specific cases of the highly linear behavior (up arrow chi) combined with a broad distribution of relaxation times, the PS method systematically vastly underestimates the value of chi. A new, improved temperature program was proposed for the PS method, eliminating the major intrinsic drawback of the originally proposed version of the PS methodology. In addition, based on the comparison between the theoretically simulated and real-life experimental data, a new approach (based on the characteristic PS dependence shape) was introduced to estimate the width of the relaxation times distribution.
Metoda pro popis strukturní relaxace ve skelných materiálech z posunu píku: přehodnocení
Keywords: aging; glass transition; kinetics; theory; thermal analysis; stárnutí; skelný přechod; kinetika; teorie; termická analýza